WOMEN AS PERPETRATORS OF FEMALE VICTIMIZATION IN RAZINAT MOHAMMED’S HABIBA (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
Victimization exists in spect of human relationship. Most research findings in African literature usually identify men as the main perpetrators of women oppression, thereby downplaying the fact that women also carry out oppressive acts against their fellow women. This study, therefore, examines women as perpetrators of women subjugation in Razinat Mohammed’s Habiba with a view to establishing that women also contribute to their ill-treatment and relegated status in the Nigerian society by victimizing one another. Habiba is purposely chosen for this study because of its portrayal of female characters that perpetrate oppression against fellow women. Foci-feminism is adopted as theoretical framework and the novel is subjected to textual analysis. This study discovers that, apart from being victims of men’s oppression, women are agents of women oppression. Hamsatun, in Habiba, represents an oppressive female character who makes lives of other women around her miserable. This study concludes that men-to-women oppression saga in African society requires a painstaking re-examination in order to end all forms of oppression against women whether it is from inter- or intra-gender perpetrators.